The Road Less Travelled: probation Trends in Canada Over the Past 30 Years - Reid, Andrew A. (Canadian journal of criminology and criminal justice, 2023)
Dramatic increases to the use of probation, particularly over the 1980-2010 period, have been identified across many Western nations. Yet Canada has experienced a very different trajectory. The volume of probation sentences imposed in Canada has declined substantially over the past 30 years. This article employs national data from the Uniform Crime Reporting Survey and Integrated Criminal Court Survey to identify factors that have contributed to this unique trend. Unlike other nations, Canada has not introduced a series of new community-based sanctions, nor has it widely embraced tough-on-crime policies. Results of the analyses in this study show that the decline in probation has come about during a period where there have been decreases in the crime rate, the volume of cases entering the court system, and the proportion of cases resulting in a guilty finding. Conversely, there has been a greater tendency for judges to include probation as part of sentencing dispositions, yet the volume of probation sentences has nevertheless declined.